2021
DOI: 10.1038/s41598-021-87216-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint molecules B7-H6 and PD-L1 co-pattern the tumor inflammatory microenvironment in human breast cancer

Abstract: B7-H6 and PD-L1 belong to the B7 family co-stimulatory molecules fine-tuning the immune response. The present work investigates the clinical effect of B7-H6 protein expression with PD-L1 status and the infiltration of natural killer cells as potential biomarkers in breast tumor inflammatory microenvironment. The expression levels of B7-H6 protein by cancer cells and immune infiltrating cells in human breast cancer tissues and evaluate their associations with PD-L1 expression, NK cell status, clinical pathologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Growing numbers of research have reported that mutually-exclusive or co-expressed patterns of B7 molecules could predict inflamed or non-inflamed TME in multiple human cancers [14,29]. For example, B7-H4 is negatively correlated with PD-L1 and identifies immuno-cold tumors in glioma [14].…”
Section: Discussionmentioning
confidence: 99%
“…Growing numbers of research have reported that mutually-exclusive or co-expressed patterns of B7 molecules could predict inflamed or non-inflamed TME in multiple human cancers [14,29]. For example, B7-H4 is negatively correlated with PD-L1 and identifies immuno-cold tumors in glioma [14].…”
Section: Discussionmentioning
confidence: 99%
“…Given co-expressed or mutually-exclusive patterns of B7 molecules predict inflamed or non-inflamed TME in multiple human cancers [ 14 , 15 ], we next assess whether co-deficiency of B7-H3 and B7-H4 predicted specific TME features. The xCell tool was used to estimate the abundance of 64 immune and stromal cell types in the TCGA database, and the abundance of these cells in the co-low, single-high and co-high groups were next compared.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, B7-H3 and B7-H4 are significantly up-regulated in PAAD tissues compared with non-tumor or normal pancreas tissues [ 12 , 13 ]. Besides, co-expressed or mutually-exclusive patterns of B7 molecules predict inflamed or non-inflamed TME in multiple human cancers [ 14 , 15 ]. However, the correlation between B7-H3 and B7-H4 expression and TIICs abundance as well as the predictive value of combined B7-H3 and B7-H4 in assessing prognosis has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The role of B7-H6 in the inflammatory tumor microenvironment design was sought via the relationship of its expression with PD-L1 and NK-TILs status. 27 The impressive results obtained with immunotherapy in other chemoresistant tumors such as melanoma and renal cancer have raised interest in the potential for using this approach in patients with gynecologic cancers. This has led to the development of a large number of clinical trials testing immunotherapy both as monotherapy and in combination with other strategies such as chemotherapy, targeted agents, or both.…”
Section: Pd-1/pd-l1/pd-l2 As Therapeutic Targets and Their Significan...mentioning
confidence: 99%